Christian generosity according to 2 Corinthians 8-9 : its exegesis, reception, and interpretation today in dialogue with the prosperity gospel in Sub-Saharan Africa - Habarurema, Viateur (Carlisle, Cumbria. Langham Monographs, 2017)
The social and religious phenomenon popularly known as the "prosperity gospel" should not be considered merely as a practical issue that needs addressed in churches, but also a matter that requires academic investigation and engagement. Dr Habarurema applies biblical scholarship, historical enquiry and contemporaneous analysis to generosity and financial reward in 2 Corinthians 8-9 and to the prosperity gospel movement. Focusing on the concepts of divine charis and autarkeia, this study provides insight into the apostle Paul's exhortations to care for the poor and vulnerable in society as a manifestation by the church, of God's compassion and grace. This book provides detailed exegesis of the chapters in question, an overview of Pentecostalism within Protestant and Roman Catholic churches in sub-Saharan Africa, comparison of the themes with their treatment by theologians throughout the history of the church and investigation of the prosperity gospel movement. The author concludes with a series of hermeneutical and theological recommendations to promote a reading which is faithful to Paul's thoughts in 2 Corinthians 8-9, fully integrated in his overall theology, and remains open to insights provided by Pentecostal hermeneutics.
Keywords: Bible.-- Corinthians, 2nd, VIII-IX.-- Criticism, interpretation, etc; Charity.-- Biblical teaching; Faith movement (Hagin).-- Africa; Africa; Pentecostalism.-- Africa